Once upon a China - Lim, C. J.; McCloy, Steve (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Once Upon a China is an unconventional architectural story of great beauty, empathy, honour and sadness. The chapters are ingenious re-imaginations of 'Dream of the Red Mansion', 'Journey to the West', 'The Water Margin', and 'Romance of the Three Kingdoms', and are conceived as specific themes of Chinese identity: domesticity, consumerism, democracy and adaptability. These four seminal pre-modern fictions contain diverse voices and philosophical perspectives on history as well as satires that have defined past developments of Chinese societies, politics and the built environment. Comics is an unorthodox but extraordinary medium for architectural speculations. The eccentric characteristics of comic-inspired drawings in this book enrich the process of conception and conceptualisation of design - their fragmented yet sequential nature proves versatile in the imagination of spatial experiences, enabling the complex story of the place, brief and building to materialise. At the same time, the politicisation of architecture through comics engenders a sense of optimism to reappraise Chinese critical thinking and design futures beyond the exuberance of non-contextual western capitalist models"--
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- China -- Themes, motives; Architecture -- China -- Comic books, strips, etc; ARCHITECTURE / General; ARCHITECTURE / Urban & Land Use Planning